On Neurotheology? Why Engage Empirical Studies on Theological Concepts - Manalili, Michael Mookie C. (Lumen et Vita, 2018)
Neurotheology can open new spaces of exploration and synthesis for human understanding. In his systematic book, Neurotheology (2018), Andrew Newberg compiles research of science that touches upon the sacred, making a strong case for an approach open to both neuro- and -theology. The following paper deals with the insights, methodology, and implications of this multidisciplinary approach. The first portion defines ‘neurotheology’ and its current scope for research. The second portion argues for the benefit of this systematic approach, which utilizes the scientific method and Hegelian sublation. The final portion explores the implications for humanity and for epistemology, particularly in the post-modern, post-religious milieu and for science as an emerging amicus theologiae. The hope of this project is to engage our ‘big questions’ once more in their complexity – to curiously explore experiences and creation, in order to peek into the efficacious Mystery we call God.